2020
DOI: 10.3390/pr8080918
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Smoking Procedures on Polycyclic Aromatic Hydrocarbons Formation in Traditional Dry Sausage Hercegovačka kobasica

Abstract: The concentrations of 16 polycyclic aromatic hydrocarbons (PAH) in smoked dry sausage Hercegovačka kobasica were investigated. The sausages were stuffed in two different casings (collagen and natural) and smoked in traditional and industrial smokehouses. The highest concentration of PAH 16 were detected in sausages in natural casings smoked in the traditional manner. The samples smoked in the industrial chamber stuffed in collagen casing showed the lowest PAH 16 content. The content of PAH 4 in sausage smoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…Higher levels of 16 EPA PAHs (609-679 µg/kg) and PAH4 (from ND to 9.90 µg/kg) were determined in Croatian dry fermented sausages by Mastanjević et al [11], in Portuguese traditional meat products (16 US-EPA PAHs = 877.37-2609.81 µg/kg; PAH4 = 3.47-6.94 µg/kg) by Santos et al [13], in Cypriot traditional meat products by Kafouris et al [8] (PAH4 = 5.9-15.2 µg/kg), as well as in dry cured meat products from Bosnia and Hercegovina by Puljić et al [12] (16 US-EPA PAHs = 145-2474 µg/kg; PAH4 = 12.7-32.5 µg/kg). In contrast, traditional meat products from Spain [9,10] and Italy [36] showed lower amounts of 16 US EPA PAHs (<100 µg/kg), while dry fermented sausages from Bosnia and Hercegovina [37] had similar amounts of 16 US EPA PAHs (<300 µg/kg), compared to the results obtained in this study. The variations in the PAHs levels could be attributed to the traditional smoking process, which is specific for each geographical area and the type of meat product.…”
Section: Resultscontrasting
confidence: 62%
“…Higher levels of 16 EPA PAHs (609-679 µg/kg) and PAH4 (from ND to 9.90 µg/kg) were determined in Croatian dry fermented sausages by Mastanjević et al [11], in Portuguese traditional meat products (16 US-EPA PAHs = 877.37-2609.81 µg/kg; PAH4 = 3.47-6.94 µg/kg) by Santos et al [13], in Cypriot traditional meat products by Kafouris et al [8] (PAH4 = 5.9-15.2 µg/kg), as well as in dry cured meat products from Bosnia and Hercegovina by Puljić et al [12] (16 US-EPA PAHs = 145-2474 µg/kg; PAH4 = 12.7-32.5 µg/kg). In contrast, traditional meat products from Spain [9,10] and Italy [36] showed lower amounts of 16 US EPA PAHs (<100 µg/kg), while dry fermented sausages from Bosnia and Hercegovina [37] had similar amounts of 16 US EPA PAHs (<300 µg/kg), compared to the results obtained in this study. The variations in the PAHs levels could be attributed to the traditional smoking process, which is specific for each geographical area and the type of meat product.…”
Section: Resultscontrasting
confidence: 62%
“…Such results are expected because of the PAH lipophilic character [35,36]. Other studies on dry smoked sausages showed a lower PAH content in the middle of the product [37][38][39], which can be related to the fact that sausages have casings (barrier between smoke and the meat product). PAH16 content in the middle of the bacon was 1294.41 µg kg −1 , 676.04 µg kg −1 on the surface and 1076.52 µg kg −1 in the skin when it was smoked in the traditional way.…”
Section: Pah Determinationmentioning
confidence: 66%
“…Šuvalija (2002) found a higher content of BaP in samples of Bosnian prosciutto from traditional compared to industrial production. A higher content of PAH compounds in smoked meat products from traditional compared to industrial production was established by Đinović et al (2008a), Puljić et al (2019), Zachara et al (2017, Kubiak and Polak-Śliwińska (2015), Mastanjević et al (2020) and in their research.…”
Section: Resultsmentioning
confidence: 77%